PEMBUATAN HAND SANITIZER ALAMI DI DESA NAMU UKUR UTARA - Juandi Al Gani Sika; Linda Eriri; Novi Novera; Qur’ani Awaliyana; Ziana Syahputri; Amal Hayati (Politeknik Negeri Sriwijaya, 2021)
The increasing outbreak of Covid-19 is a serious epidemic that is being faced by the people of Indonesia, so it is mandatory to implement the